Learning styles of diploma students at a public university in Malaysia post COVID-19 pandemic / Noraziah Azizan ... [et al.] - Azizan, Noraziah; Ab Manan, Nor Ashikin; Yusof, Johana; Mohammad Patel, Iza Faradiba (Universiti Teknologi MARA, Kedah, 2024)
The education system worldwide underwent a drastic change during the Covid-19 pandemic. Online distance learning or ODL was adopted to limit face-to-face interactions and minimize the spread of the contagious diseases. Educators and students had to adapt their teaching methods and learning styles respectively, during the pandemic. However, now that the world is already in the endemic phase and online classes have been replaced by face-to-face classes, the question has been raised on whether the situation has changed the way the students are learning. This study aims to investigate the learning styles of diploma students at a public university in Malaysia to determine whether their learning styles are different during and after the COVID-19 pandemic. The participants in the study are 100 diploma students at UiTM Perak. The data were collected through the distribution of questionnaire adapted from VAK (Chislett & Chapman, 2005). It was found that most of the participants are visual learners and preferred VISUAL learning style. In addition, most of the students (76%) felt that they have adapted to the changes of the learning environment during and after the Covid-19 pandemic and have changed their learning styles accordingly. To the question whether they prefer Online Distance Learning (ODL) or face-to-face learning environment, only ten (10%) of the students stated that they prefer ODL while the rest prefer face-to-face learning environment. The findings of the research will contribute valuable insights for educators, policy makers and the learning institutions to enhance learning and teaching quality and to support the diverse learning needs of diploma students.